Original articleUltrastructural picture of blood vessels in muscle and skin biopsy in CADASIL - Lewandowska, Eliza; Leszczyńska, Anna; Wierzba-Bobrowicz, Teresa; Skowrońska, Marta; Mierzewska, Hanna; Pasennik, Elżbieta (Folia Neuropathologica, 2006)
CADASIL (cerebral autosomal dominant arteriopathy with subcortical infarcts and leucoencephalopathy) is an inherited systemic vascular disorder affecting mainly the central nervous system. We performed detailed ultrastructural examination of the small vessels in the skin and skeletal muscle of a 51-year-old patient with bilateral cerebral white matter lesions, who had a history of two ischaemic strokes. The arterioles were characterized by degeneration and loss of vascular smooth muscle cells (VSMCs). GOM deposits, varied in size and shape, were located in the neighbourhood of the smooth muscle cells, often within an infolding of the cell membrane. No apparent correlations between presence, size or number of GOM deposits and damage severity of vascular smooth muscle cells were seen. Moreover, in some capillaries there were GOM deposits which were seen in the basement membrane near pericytes and endothelial cells. On the other hand, lesions of VMSCs and/or endothelial cells were also visible on the sections of blood vessels devoid of GOM deposits. Genetic tests detected a mutation in exon 4 of the Notch3 gene. It confirmed the initial diagnosis which had been suggested on the basis of the clinical and MRI findings.